Random Forest profiling attack on advanced encryption standard. (1st January 2014) - Patel, Hiren; Baldwin, Rusty O.
Random Forest, a non-parametric classifier, is proposed for byte-wise profiling attack on advanced encryption standard (AES) and shown to improve results on PIC microcontrollers, especially in high-dimensional variable spaces. It is shown in this research that data collected from 40 PIC microcontrollers exhibited highly non-Gaussian variables. For the full-dimensional dataset consisting of 50, 000 variables, Random Forest correctly extracted all 16 bytes of the AES key. For a reduced set of 2, 700 variables captured during the first round of the encryption, Random Forest achieved success rates as high as 100% for cross-device attacks on 40 PIC microcontrollers from four different device families. With further dimensionality reduction, Random Forest still outperformed classical template attack for this dataset, requiring fewer traces and achieving higher success rates with lower misclassification rate. The importance of analysing the system noise in choosing a classifier for profiling attack is examined and demonstrated through this work.